Uji Aktivitas Antibakteri Ekstrak Etanol Bawang Dayak (Eleutherine palmifolia (L.) Merr) Terhadap Bakteri Staphylococcus aureus - Warsiti, Warsiti; Wardani, Sisca Dwikusuma; Ramadhan, Ardea Achmad; Yuliani, Ratna (Pharmacon: Jurnal Farmasi Indonesia, 2018)
Staphylococcus aureus is an infectious bacteria with pus because of tissue damage. Infectious diseases caused by S. aureus include wound infections, ulcers, pimples, and impetigo. Dayak onions have the benefit of being antibacterial. This research aims to study the antibacterial activity of ethanolic extract of Dayak onions against  Staphylococcus aureus. The antibacterial study was carried out using the disk diffusion method. Identification of bacteria by Gram staining showed Gram-positive bacteria which can ferment mannitol with the mannitol test. A bacterial sensitivity test was conducted using three antibiotics i.e. cefoxitin 30μg, vancomycin 30μg, and linezolid 30μg. The bacteria was sensitive to all of the three antibiotics, with the inhibitory zone of 23.5 mm; 17 mm and 27.5 mm, respectively. Vancomycin 30μg was used as a positive control, resulted in average diameter of the inhibitory zone of 17.83  2.25 mm, whereas a control solvent DMSO (Dimethyl sulphoxide) did not produce zones. The ethanolic extract of Dayak onion in the concentration of 25%; 50%; 75% and 100% showed the average diameter of inhibitory zones of 8.17  0.29  mm; 10.67  1.44 mm; 10.33  1.53 mm; and 12.33  1.61  mm, respectively